Design of 4 servo robot arm with Blynk Control - Putra, Willy; Piarsa, I Nyoman; Wibawa, Kadek Suar (Hexatech: Jurnal Ilmiah Teknik, 2026)
The development of robotics technology today is experiencing rapid progress through innovations in various fields, such as the application of artificial intelligence (AI), advanced sensors, and autonomous control systems. Robots are now not only used in the industrial infrastructure sector, but also in the fields of health, transportation, agriculture, and everyday life to help humans complete various tasks. This study discusses the design of a robot arm with four servo motors based on an ESP8266 Wi-Fi microcontroller controlled through the Blynk application. The purpose of this study is to automate the movement of the robot arm in performing a task and to compare its performance with and without the use of a Pulse Width Modulation (PWM) controller PCA9685 module. The system development stages include design analysis, device design and assembly, movement programming, and system testing. The results show that the movement of the robotic arm without PCA9685 has an accuracy rate of 99.323%, while with PCA9685 it reaches 99.77%. The average accuracy percentage increased by 0.447% on the robot arm with the PCA9685 and reduced the complexity of the cables connected to the breadboard by 57.14%.